Experimental Study of Enzyme-Induced Carbonate Precipitation for High Temperature Applications by Controlling Enzyme Activity. Issue 6 (1st June 2022) - Wang, Hengxing; Miao, Linchang; Sun, Xiaohao; Wu, Linyu; Fan, Guangcai
Abstract: Biomineralization is a popular reinforcement technology, but which is rarely studied at high temperatures. Some potential application targets are high-temperature environments. So it's essential to study the feasibility of biomineralization at high temperatures. In this article, plant urease was selected as a cost-effective enzyme for enzyme-induced carbonate precipitation (EICP) at high temperatures. Urease activity and urease enzyme-induced carbonate precipitation were studied as a function of temperature, urease concentration, and N-(n-butyl)-thiophosphoric triamide (NBPT) addition. The effects of reaction time, number of perfusions, urease concentration, temperature, and NBPT addition on the curing efficiency of sand columns were studied by unconfined compressive strength tests and by determining the resulting concentration of CaCO3 . The results demonstrated that the urease could maintain a stable activity at temperatures below 65 °C. At temperatures higher than 65 °C, urease was gradually inactivated with increasing temperature, which would influence the yield of precipitation. However, increasing the urease concentration and the number of infusions could ensure the sand solidified with adequate CaCO3 . In addition, NBPT was proposed as a new way to control urease activity, which resulted in a high UCS of the sand columns formed at high temperatures. This paper bears out that sand solidification can be achieved at high temperatures using EICP and lays the foundation for future application of EICP at high temperatures.